Macmillan encyclopedia of energy - Zumerchik, John (Macmillan Reference USA, 2001)
"These volumes provide a snapshot of the history and science of energy production, conservation, and use. Multidisciplinary in scope, the 253 signed and lavishly illustrated articles cover topics ranging from biofuels and bicycles to steam engines and thermodynamics. The work ends with a fascinating energy time line that puts major events in the history of energy into context."--"Outstanding Reference Sources," American Libraries, May 2002.